2009
DOI: 10.1007/s00417-009-1122-6
|View full text |Cite
|
Sign up to set email alerts
|

Tafluprost protects rat retinal ganglion cells from apoptosis in vitro and in vivo

Abstract: These data suggest that tafluprost has an anti-apoptotic effect in RGCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…24 Dong et al found that tafluprost induced concentration-dependent relaxation of precontracted isolated rabbit ciliary arteries, but by a mechanism that was independent of endothelial-derived factor. 25 28 In a more recent study, commercially available preservative-free tafluprost was applied directly onto the surface of a rat retinal explant culture. 29 The authors noted a reduction of both neuronal and total cell loss from the retinal ganglion cell layer at 4 days ex vivo, compared to controls, although no effect was found after 1 week.…”
Section: Tafluprost Efficacy and Safety -Preclinical And Animal Studiesmentioning
confidence: 99%
“…24 Dong et al found that tafluprost induced concentration-dependent relaxation of precontracted isolated rabbit ciliary arteries, but by a mechanism that was independent of endothelial-derived factor. 25 28 In a more recent study, commercially available preservative-free tafluprost was applied directly onto the surface of a rat retinal explant culture. 29 The authors noted a reduction of both neuronal and total cell loss from the retinal ganglion cell layer at 4 days ex vivo, compared to controls, although no effect was found after 1 week.…”
Section: Tafluprost Efficacy and Safety -Preclinical And Animal Studiesmentioning
confidence: 99%
“…Another study identified a direct anti-apoptotic effect of tafluprost on cultured RGCs and rat RGCs after optic nerve crush. 27 Our results warrant further experiments to explore the potential neuroprotective mechanism of tafluprost in this model. Regarding the regional differences in retinal thickness and FG-labeled RGCs, the retinal thickness was significantly different in several comparisons between different regions by OCT.…”
Section: Discussionmentioning
confidence: 80%
“…Some studies have reported the effect of tafluprost on ocular blood flow [22][23][24][25][26] and neuroprotection. 27,28 In this study, we examined the relationship between retinal injury after an intravitreal injection of ET-1 in the rat eye and the dose of ET-1. Subsequently, using the lowest dose of ET-1 that caused surely retinal injury, we examined the neuroprotective effect of tafluprost on ET-1-induced retinal injury in the rat.…”
mentioning
confidence: 99%
“…Между тем аналоги простагландинов в силу опосредованного антиоксидантного эффекта способны уменьшать токсичность БАХ в срав-нении с гипотензивными каплями из других фар-макологических групп [18,21,37]. Назначение препаратов «искусственной слезы» с гиалуроно-вой кислотой вдвое снижает токсичность БАХ в отношении поверхностных эпителиальных кле-ток [7].…”
Section: Doi: 1017816/ov9259-68unclassified